A Smart Artificial Finger with Multisensations of Matter, Temperature, and Proximity. Issue 7 (11th June 2018) - Zhao, Shuai; Zhu, Rong
Abstract: Smart robots interact with their environment or collaborators through acquiring information from their visual, acoustic, and tactile sensing systems, which are developed into a high sophisticated stage. However, expedient and fast sense perceptions for safety and intelligent control of collaborative robots still remain great challenges. Here, a smart artificial finger with multisensations of matter, temperature, and proximity, which enriches its sensory system for comprehensive learning of the object it touches is proposed. The finger sensor is composed of two thermosensitive platinum ribbons on a polyimide substrate, which detect thermal properties of surroundings, that is, temperature and thermal conductivity, from which surrounding matter is identified. The sensor has a large range of detectability for discriminating diverse matters from cotton to metal, perceiving temperature stimulus and approaching object. The applications of identifying matter type, sensing proximity distance, and monitoring moisture and temperature of human skin are demonstrated. The smart finger provides promising approaches to enhance intelligence and safety of smart robots. Abstract : A smart artificial finger with multisensations of matter type, temperature, and proximity is proposed. The finger sensor, based on thermosensation, is fast in detecting the thermal properties of its surroundings, from which the surrounding matter is identified and the approaching distance to an object is detected. The smart finger provides promising approaches to enhancing safety and intelligence of human–machine interaction.